"RELATIVE MOVEMENTS OF REAL WAGES AND OUTPUT"—HOW DOES KEYNES'S 1939 ESSAY RELATE TO HIS THEORY OF EFFECTIVE DEMAND?. Issue 2 (7th March 2017) - Hartwig, Jochen
Abstract : John Maynard Keynes's essay "Relative Movements of Real Wages and Output" is widely believed to be an important amendment to his General Theory because, in this essay, Keynes relaxed his core assumption of decreasing marginal returns to labor. I discuss the reasons that prompted Keynes to do so and then examine the consequences of replacing decreasing with non-decreasing returns for the model of effective demand from chapter 3 of the General Theory . I conclude that non-decreasing marginal returns do not sit comfortably with the principle of effective demand. The view that Keynes's1939 essay constitutes an important amendment to his General Theory has thus to be put into perspective.